Development of a Model for Experimental Data Treatment of Diffusion and Activation Limited Polarization Curves for Magnesium and Steel Alloys. Issue 11 (1st January 2017) - Stephens, L. I.; Perry, S. C.; Gateman, S. M.; Lacasse, R.; Schulz, R.; Mauzeroll, J.
Abstract : Potentiodynamic polarization curves are often performed to characterize the bulk corrosion properties of a material in terms of its corrosion potential, rate, and Tafel kinetics in a given environment. This requires approaching them as one of two extreme cases, with purely activation or diffusion controlling the measured currents. For the intermediate behavior displayed by many real samples, making this assumption is a significant source of error. In this work, a finite element model has been developed which considers both of these contributions simultaneously for experimental data with a broad material scope. This has been used to examine both extremely corrosion vulnerable samples in two magnesium alloys and extremely corrosion resistant samples in two steels. The effectiveness of several goodness of fit statistics in comparing the similarity between experimental and simulated data has also been assessed.